The Effectiveness of Group Dialectical Behavior Therapy on Reducing the Divorce Propensity and Self-Differentiation in Couples with Marital Conflict - Esmaeili, Ameneh; Asgari, Parviz; Ehteshamzadeh, Parvin; Safarzadeh, Sahar (Advances in Nursing & Midwifery, 2024)
Abstract Introduction: As divorce rates continue to rise, there is a critical need to explore effective interventions that can strengthen marriages and reduce family breakdown. This study aimed to investigate the effectiveness of group dialectical behavior therapy (DBT) in reducing the divorce propensity and self-differentiation in couples with marital conflict referred to the family court in Karaj City. Methods: The present study employed a quasi-experimental pretest-posttest control group design. The target population comprised all couples who filed for divorce at the Karaj Family Court in 2023. A purposive sample of 32 participants meeting the study’s inclusion criteria was randomly assigned to experimental and control groups (n=16 per group). Participants completed the Divorce Propensity Questionnaire (DPQ) and Self-Differentiation Inventory (SDI) pre- and post-intervention. The experimental group received sixteen 90-minute group Dialectical Behavior Therapy (DBT) sessions. Data were analyzed using analysis of covariance (ANCOVA) in SPSS-27. Results: The results revealed significant positive effects of group DBT. The results revealed significant positive effects of group DBT. The analysis shows that the Dialectical Behavioral Therapy group had a significantly lower divorce propensity score (89.31 ± 23.37) compared to the control group (123.13 ± 24.14) (F= 37.73, P<0.001). Moreover, their self-differentiation score was significantly higher (175.31 ± 16.85 vs. 125.75 ± 11.06) (F=99.49, P<0.001). Conclusions: Based on the study's results, group DBT can be considered an effective intervention to reduce the divorce propensity and improve self-differentiation in couples referred to the family court.